ANALISIS BELANJA MODAL, INVESTASI, DAN TENAGA KERJA TERHADAP PERTUMBUHAN EKONOMI SULAWESI SELATAN (CAPITAL EXPENDITURES ANALYSIS, INVESTMENTS, AND EMPLOYMENT ON ECONOMIC GROWTH SOUTH SULAWESI) - Basri Bado (Fakultas Ekonomi Universitas Negeri Jakarta, 2015)
ABSTRACT The aim of this study was to determine the influence of Capital Expenditure and Investment, and Employment on economic growth in South Sulawesi. This study uses time series data (time series) in 2001-2013. Data collected through observation and documentation. Data were analyzed using multiple linear regression analysis by the method of ordinary least squares (OLS). The results showed that the variable Capital Expenditures, Investment, and Labour significant effect on economic growth in South Sulawesi. Capital Expenditure Partially variables, and variables of Labor has a significant influence on the economic growth of South Sulawesi. While variable investments significantly negative effect on economic growth in South Sulawesi. Keywords: Capital Expenditures, Investment, Employment, Economic growth.